Abundance and survival estimates of the southeastern Pacific humpback whale stock from 1991–2006 photo-identification surveys in Ecuador - Félix, Fernando; Castro, Cristina; Laake, Jeffrey L. (J. Cetacean Res. Manage., 2020)
Southeastern Pacific humpback whales (Breeding Stock G) breed along the northwestern coast of South America and farther north up to Costa Rica. Photo-identification surveys conducted aboard whalewatching vessels during the migration/breeding season from June to September between 1991 and 2006 off the coast of Ecuador (2°S, 81°W) have produced a database of 1,511 individual whales. Comparisons of photographs produced 190 between-year re-sightings of 155 individual whales. Closed and open capture-recapture models were used to estimate abundance and survival. The best estimate of abundance in 2006 with the Chapman modified-Petersen was 6,504 (95% CI: 4,270–9,907; CV = 0.21). Abundance estimates from open population models were considerably lower due to heterogeneity in capture probability which produced a ‘transient’ effect. Our best estimate of true survival was 0.919 (95% CI: 0.850–0.958). Heterogeneity most likely occurred from inter-annual variation in sampling and unknown structure and variation in the migration timing and corridor. A more extensive collaborative effort including other wintering areas further north as well as integrating breeding-feeding data will help to reduce heterogeneity and increase precision in abundance and survival estimates.